DAMPAK PERUBAHAN BUDAYA DI KOTA BAUBAU TERHADAP PEMBELAJARAN DI SEKOLAH DASAR - Haliadi; St Nurhadijah; Windi Risma Yanti (CV. ADIBA AISHA AMIRA, 2026)
This research examines the impact of cultural shifts in Baubau City on the learning patterns of elementary school students. As the former center of the Buton Sultanate, Baubau possesses a rich cultural heritage, yet globalization has introduced digital behaviors that challenge traditional educational values. The study identifies a decline in the application of local philosophies, such as